Prevalence of otitis media with effusion in first and second grade primary school students and its correlation with BCG vaccination - Keles, E; Kaygusuz, I; Karlidag, T; Yalçin, S; Açik, Y; Alpay, HC; Sakallioglu, Ö (Elsevier Ireland Ltd, 2004)
Objective: The object of this study was to determine the prevalence of otitis media with effusion (OME) in first and second grade primary school students, to analyze the causes of the difference in the prevalence, to define the effect of OME on the academic performance of the children and to investigate a correlation between the prevalence of OME and Bacillus Calmette-Guerin (BCG) vaccination. Study plan and methods: The study was conducted during the September-November, 2002 period in Elazig. A total of 3675 clinically healthy primary school children attending primary schools in the central district of Elazig, living in the same region and of a similar socioeconomic status and age group were included in the study. Of the 3675 children, 2042 were in their first and 1633 in their second grade of primary school. The routine ear-nose and throat examinations of the children were carried out at their schools by the same medical team. The tympanometric test was performed in children diagnosed with OME following otoscopic examination. A scale measuring the academic performance of the children was developed. This scale was filled in by the student's teachers prior to physical examination. Results: OME was diagnosed in 64 out of 2042 (3.1%) first grade and in 25 out of 1633 (1.5%) second grade students. The difference between the percentages of OME in first and second grade students was statistically significant (P < 0.05). The frequency of other ear-nose and throat pathologies accompanying OME was similar to those in children without OME. There was no statistically significant difference between the academic performances of children with and without OME (P > 0.05). Conclusion: The analysis of risk factors for OME revealed no difference between first and second grade students. The reason for the difference in the prevalence of OME between first and second grade students may be the positive effect on the immune system of the BCG vaccine which had been administered to the second grade students 4 months previously. (C) 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: otitis media with effusion; academic performance; prevalence; BCG vaccine